Integrating Fiqh evidences in the recommendation for management of diabetes during Ramadan - Shahar, Mohammad Arif; Che Mohamad, Che Anuar; Hisham, Ahmad Irfan Ikmal; Omar, Ahmad Marzuki (Malaysian Endocrine & Metabolic Society (MEMS), 2016)
Introduction: In the year 2005, The American Diabetic Association (ADA) published the Recommendations of Management of Diabetes During Ramadan and an update was released in 2010. In 2015, another update was produced by the International Group for Diabetes and Ramadan (IGDR). One of the issues addressed in the update was on the risk stratification for patients planning to fast during the holy month. Despite this stratification, patients with diabetes choose to continue to observe their fast regardless of the risk, as shown in the CREED study. Lack of Islamic Jurisprudence (Fiqh) evidences presented in the document, issue on fasting as a personal choice and lack of clinical evidences pertaining to diabetes and Ramadan may account for the low acceptance among Muslims.